Synthesis of 2,4-dihydro-3H-1,2,4-triazole-3-thione and 2,3-dihydro-1,3,4-thiadiazole derivatives - Rollas, Sevim (Marmara Pharmaceutical Journal, 1986)
Synthesis of 2,4-dihydro-3H-1,2,4-triazole-3-thione and 2,3-dihydro-1,3,4-thiadiazole derivatives